RECURRENT TEMPOROMANDIBULAR JOINT ANKYLOSIS CAUSED BY OLD FRACTURE: A CASE REPORT - Isya Wahdini, Siti; Idamatussilmi, Fina (Universitas Airlangga, 2025)
Highlights: Adequate physiotherapy is essential to prevent the recurrence of temporomandibular joint ankylosis. Surgical treatment alone is insufficient without proper postoperative physiotherapy and patient compliance. Abstract Introduction: Temporomandibular joint (TMJ) ankylosis can greatly impact a child's nutrition, mental health, and craniofacial development. Trauma is the main cause. Early and proper treatment is crucial to avoid long-term issues and reoccurrence. Case Illustration:An 11-year-old girl presented with limited mouth opening and lower jaw pain three years after falling down the stairs. She underwent gradual TMJ distraction using bite blocks under general anesthesia followed by weekly physiotherapy, but her symptoms recurred after four months. A CT scan revealed left TMJ synarthrosis and condylar deformity. With improved adherence to physiotherapy, she achieved significant mouth opening and remained recurrence-free for six months.. Discussion: Gradual distraction with bite blocks, combined with regular physiotherapy, can improve joint mobility and muscle function while lowering the chances of re-ankylosis. This approach offers a less invasive option than surgery, which is especially valuable for children whose growth must be preserved. Closed procedures with structured rehabilitation are preferred because they result in fewer complications and require fewer follow-up appointments. Conclusion: The effectiveness of a non-invasive approach combining gradual distraction and physiotherapy in managing TMJ ankylosis is presented. The success of this treatment relies heavily on the patient's motivation and commitment. Early conservative treatment could be the main strategy for pediatric cases, potentially delaying or avoiding surgery. Continuous education and monitoring are key to achieving long-term success and preventing relapse.